Uso do tempo de cuidadores de crianças e adolescentes com deficiência: organização da rotina familiar para o cuidado - Letícia Rocha Dutra (2020)
The studies presented in this thesis aimed to investigate the time use profile of caregivers of children and adolescents with and without disabilities and the factors that affect the organization of the routine for the care of the child. The first study compared the time use profile of caregivers of children with cerebral palsy (CP = 69), Autism Spectrum Disorder (ASD = 61) and typical development (TD = 54). Caregivers of these child/adolescent (4 to 18 years old) filled out 2 diaries of the time use, one for weekdays and one for weekends, reporting on primary (main) and secondary (concomitant with primary) activities. Medians of time spent by caregivers were compared using the Kruskal-Wallis test. Mann-Whitney test with Bonferroni correction was used for posthoc bivariate comparisons. The time categories that showed significant differences between the three groups had the total time spent dichotomized (“spend more time”; “spend less time”). The average score, odds ratio and 95% confidence interval were estimated by logistic regression models adjusted for confounding variables. The time spent caring for the child was greater in the group of caregivers of children/adolescents with disabilities on weekdays, on weekends, in primary and secondary activities, when compared to caregivers in the group with TD. Differences between these groups (with and without disabilities) were also found in the time spent on paid work and transportation (primary activities) on weekdays; time spent on personal care (primary activity) and socialization (secondary activity) on weekend days. Regression models showed that the variable “group” was the one that most interfered with the time spent in care. The second study aimed to examine the determinants of the time spent in the care of children and adolescents with CP, ASD and TD. The participants (n = 184) were the same caregivers for children/adolescents in the three groups that comprised study 1. The dependent variable was the time spent in caring for children/adolescents measured by a time-use diary. The measured independent variables included socioeconomic level (SES) of the families and the child's functioning. In addition, parents reported the number of adaptations used by their children and the number of hours they received help in the care of this child/adolescent. A theoretical model was built with the hypothetical direct and indirect relationships between the variables, and tested using structural equation modeling (SEM). The three models adjusted to the data, explaining 29% of the variation in time spent in care in the CP group, 44% in the ASD group and 78% in the TD group. The adaptations had an indirect effect on the care time through their effect on functioning (CP group). The SES indirectly impacted functioning through its effect on the use of adaptation (ASD group). The third study of this thesis aimed to identify and analyze the accommodations used by mothers of children and adolescents with ASD to care for their child. Ten mothers of children and adolescents with ASD between the ages of 4 and 13 with different levels of severity, answered a structuring question "Tell me, please, how is your routine with your child?" The speeches were analyzed with thematic analysis and two central themes summarized the accommodations used in the daily routine of caring for the child: "I do it for my child" and "I do it with my child". Mothers do activities for their children to deal with the time available; with the manifestation of your children's symptoms; and for not believing their children are able to carry out the activities alone. Mothers also do some tasks with their child, creating opportunities for practice and enabling their participation by fragmenting activities into stages and offering verbal and visual cues. The three studies from this thesis showed that the activity of caring for the child is complex and presents itself as imperative in the routine of caregivers, with different types of accommodation being used to meet the needs of the child with disability. The combination of methods used in the three studies made it possible to contribute in different ways to the existing knowledge and to fill in some gaps in the literature. Investigating the profile of the time spent by caregivers of children with disabilities and the time spent on child care enable rehabilitation professionals to build family-centered practices, working in partnership with caregivers and contributing to the construction of more sustainable routines, where needs of all family members can be considered.